AN EVALUATING EFFECTIVENESS STRATEGIC IMPLEMENTATION: The Case of PT SUCOFINDO Padang Branch Area - Ade Azis Kusnaya; Syukri Lukman; Syafrizal Syafrizal (Halu Oleo University, 2022)
Nowadays, effectiveness strategic implementation has challenged various company due to unpredictable business situation. Therefore, the company should measure how accurate the effectiveness strategy which was implemented. This study aims to analyze the effect of leadership, resource allocation, and employee engagement on it through organizational commitment. Saturated sampling technique used in this study by the amount of 52 employees recorded as participants. Previously, the data were collected through online method and assisted by g-form questionnaires, then it analyzed with Structural Equation Model (SEM) technique from IBM AMOS 23.0 software. The study found that in the direct effects there are three relationships stated not significant, but fourth of them. Further, mediating contributions of organizational commitment only success in the relation of employee engagement on effectiveness strategic implementation, and the other are rejected due to not contributes optimally.